Stool pH and Short/Branched Chain Fatty Acids in Infants Receiving Extensively Hydrolyzed Formula, Amino Acid Formula, or Human Milk Through Two Months of Age (P11-076-19). (13th June 2019) - Kok, Car Reen; Brabec, Bradford; Chichlowski, Maciej; Harris, Cheryl; Moore, Nancy; Wampler, Jennifer; Vanderhoof, Jon; Rose, Devin; Hutkins, Robert
Abstract: Objectives: Infant feeding influences early development of the gut microbiome, colonization pattern, and community structure. Metabolites, including short- and branched-chain fatty acids (S/BCFA) (e.g., butyrate, propionate), produced by colonic bacteria serve as signaling molecules, influence immunity, and reduce luminal pH in the gastrointestinal environment. The objective of this study was to evaluate stool S/BCFA and pH in infants fed with different sources of dietary protein. Methods: In this multicenter, double-blind, controlled, parallel-group, pilot study, healthy term infants were randomized to receive one of two infant formulas (IF): amino-acid based (AAF; n = 25) or extensively hydrolyzed cow's milk protein (EHF; n = 28) from Baseline (1-7 days of age) up to 60 days of age. A human milk reference group (HM; n = 25) received mother's own milk over the same period. Diethyl ether extractions of S/BCFA from stool samples (Baseline, Day 30, and Day 60) were quantified by gas chromatography (Clarus 580; PerkinElmer) using a fused silica capillary column (Nukol 30m × 0.25mm id × 0.25μm film). Mean stool S/BCFA (μmol/g) and pH were analyzed by repeated measures analysis of variance (ANOVA). Results: Complete stool data (all study time points) were available for 49 participants. Stool pH (∼6) was similar among groups at Baseline with no significant changes for HM and EHF groups through Day 60. The AAF group was significantly higher at Days 30 and 60 (Figure 1). Total SCFA were similar for all groups through Day 60. Butyrate increased significantly from Baseline to Day 60 in the EHF group ( P  = 0.026) and was significantly higher vs HM at Days 30 and 60 ( P  = 0.0009 and 0.0004 respectively). Butyrate was significantly higher for AAF vs HM at Day 60 only ( P  = 0.038). Propionate was significantly higher for EHF and AAF at Day 30 ( P  = 0.0009 and < 0.0001 respectively) and AAF only at Day 60 ( P  = 0.005) vs HM. Total and individual BCFA increased for AAF and EHF groups vs HM through Day 60. Conclusions: Distinct patterns of pH and microbial metabolites were demonstrated for infants receiving mother's own milk compared to amino acid-based or extensively hydrolyzed protein formula. Providing different sources of dietary protein early in life may influence gut microbiota and metabolites. Funding Sources: Mead Johnson Pediatric Nutrition Institute. Supporting Tables, Images and/or Graphs: